Competence-based Educational Design Model for Medical Sciences Based on the Community of Inquiry - Mahnaz Fatemi Aqda; Javad Hatami; Soleiman Ahmady; Ebrahim Talaee (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
Introduction: Achieving competence as the main goal in medical education requires a dynamic and active learning process that includes the characteristics of a community of inquiry framework. This theoretical framework provides an overall and coherent structure of an interactive educational experience with a focus on the learning process. Therefore, the purpose of this research was to develop a competency-oriented educational model for medical sciences based on the framework of the community of inquiry. Methods: This was a qualitative and quantitative research. The qualitative part was conducted using qualitative content analysis of documents and focus group discussions, while the quantitative part involved internal validation of the educational design model through a descriptive survey method (based on experts' opinions) and a researcher-made questionnaire. The sampling method was purposeful, focusing on specific or unique cases continuing until theoretical saturation was reached. Results: Using qualitative content analysis (36 documents, 33 articles, and three books) and focus group discussions (with the participation of 14 experts in medical education), the dimensions of competence, principles of competency-based medical education, and principles of inquiry community were identified. Based on theoretical foundations, these were categorized into three domains: affective, cognitive-skills, and metacognitive, along with their subcategories. The alignment of these dimensions led to the formation of a competency-based medical education model, grounded in the inquiry community framework. Internal validation of the developed model was conducted using a researcher-made questionnaire and the participation of 14 experts in educational technology and medical education. According to the specialists' opinions, the developed model achieved a relatively high internal validity (T=14.52, P<0.0001). Conclusion: In this study, the competency-based educational design model for medical education, based on the inquiry community, exhibited appropriate design and organization, flexibility, and adaptability to individual learning needs, even in unpredictable situations within medical education. Its design and organization can be continuously refined and improved throughout the educational experience. Given that it achieved a relatively good internal validity according to the opinions of specialists in medical education and educational technology, it can be introduced as a suitable model in the field of competency-based medical education.